A BIOAVAILABILITY STUDY OF INDONESIAN GENERIC TABLET OF CAPTOPRIL IN HEALTHY VOLUNTEERS - Nugroho, Agung Endro; Hakim, Arief Rahman; ., Purwantiningsih; Hakim, Lukman (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Captopril is a selective inhibitor of angiotensin-converting enzyme (ACE) and is formulated by several pharmaceutical companies in Indonesia. This study was conducted to compare the bioavailability of a captopril tablet with reference products in healthy volunteers. The relative bioavailability of captopril was determined in single dose, randomized, crossover, and two-phase studies. The relative bioavailability of the test product (a generic captopril 50 mg tablet) with respect to the reference product was determined. Twelve healthy volunteers in two groups took part in these studies and took either the test or reference tablets in the first phase and received the other tablet in the second phase of each study. The bioavailability parameters include the peak concentration of captopril in serum (Cmax); the time to achieve the peak concentration (Tmax); and the area under the curve of captopril in serum versus time. Non-compartmental analysis on observed concentration versus time data has resulted in the mean value of Cmax of 545.26 ± 22.90 ng/mL (test product) and 548.91 ± 25.07 ng/mL (reference product) and mean Tmax of 1.13 ± 0.08 hours (test product) and 1.08 ± 0.08 hours (reference product), mean of AUC0-7 value of 1820.51 ± 75.31 ng. hour/mL (test product) and 1822.09 ± 99.29 ng. hour/mL (reference product), and mean of AUC0-inf value of 1967.83 ± 95.65 ng. hour/mL (test product) and 1996.94 ± 124.52 ng. hour/mL (reference product). Based on the data, it can be concluded that there is no significant difference (p>0.05) in bioavailability between both captopril Tablet (test and reference product).Key words: Bioequivalence, Captopril, HPLC, Human serum, Generic